Crescimento da tilápia do nilo (Oreochromis niloticus) em sistema de aquaponia - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The objective of this work was to evaluate the growth of tilapia juveniles (Oreochromis niloticus) submitted in three different densities, and the growth of smooth lettuce (Lactuca sativa L.), curly lettuce (Lactuca sativa), watercress (Nasturtium officinale) and chicory (Cichorium intybus) in aquaponics system. This experiment was carried out in the greenhouse of the Fish and Aquaculture Laboratory (LAPA) of the Zootechny course of the Federal University of Pampa (UNIPAMPA), campus Dom Pedrito-RS, with a duration of 35 days. The experimental units were arranged in three aquaponics stands experimental units with a capacity of 60L. The experimental design consisted of three treatments and three replications where was used three densities (T1 8, T2 12 and T3 16 animals per treatment), and 10 units of each plant species per treatment. Feeding was done twice a day (9 AM and 4 PM). The design was completely randomized. The parameters analyzed in the animals were weight, and total and pattern lengths, in the vegetables, root length, leaf length and leaf width. Were also monitored water quality parameters such as temperature, alkalinity, conductivity, dissolved oxygen and total ammonia. The averanges were submitted to analysis of variance and "F" test, at a significance level of 5%. The averages were compared by the Tukey test. The statistical software used was the R (2011). The growth results of the animals did not present significant differences (P > 0.05), and in the vegetables the watercress of the T1 presented a smaller root length, the flat lettuce of the T2 presented significant difference (P <0.05), with a longer root length, and the chicory of the T3 had lower leaf height. The mean temperature was 23.77 ± 4.06, dissolved oxygen of 5.5 ± 1.32 and total ammonia at 1.75 ± 0.85. It is concluded that the increase of the density of the animals does not influence the growth of tilapia juveniles, and can be adopted the greater density in a production system, and that the higher density of animals resulted in sufficient nutrients for the development of the four plant species. All the treatments presented a satisfactory water quality for the crops, making the plants efficient in the removal of ammonia from the water system. Demonstrating that the aquaponic system can be used to raise fish and plants together.
Growth of nile tilapia (Oreochromis niloticus) in aquaponics system
Keywords: Hidroponia; Densidade de estocagem; Qualidade da água; Hydroponics; Storage Density; Water Quality; Aquicultura; Aquiculture; CNPQ::CIENCIAS AGRARIAS